1999
DOI: 10.1136/hrt.82.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of atrial septal defects in adults with the Amplatzer septal occluder

Abstract: Objective-To assess the eYcacy and complications of device occlusion of atrial septal defects in adults, using the Amplatzer septal occluder (ASO). Design-A prospective interventional study. Setting-Paediatric cardiology departments in two European teaching hospitals. Patients-The first 20 patients accepted for atrial septal defect device occlusion, on the basis of transoesophageal echocardiography. Sixteen patients had larger defects with right heart dilatation, while the primary indication for closure in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 9 publications
1
32
0
5
Order By: Relevance
“…9 -12 However, in a recent study by Windecker et al 13 using 5 different types of closure devices, the periprocedural complication rate was 10% in 78 patients, including embolization of device parts, periprocedural transient ischemic attack (TIA), or stroke caused by air embolism, cardiac tamponade, and retroperitoneal hematoma. Initial results with the Amplatzer occluder in children 14 -16 and adults 17 with ASD and PFO 18 were promising in terms of efficacy and safety.…”
mentioning
confidence: 98%
“…9 -12 However, in a recent study by Windecker et al 13 using 5 different types of closure devices, the periprocedural complication rate was 10% in 78 patients, including embolization of device parts, periprocedural transient ischemic attack (TIA), or stroke caused by air embolism, cardiac tamponade, and retroperitoneal hematoma. Initial results with the Amplatzer occluder in children 14 -16 and adults 17 with ASD and PFO 18 were promising in terms of efficacy and safety.…”
mentioning
confidence: 98%
“…In patients with secundum ASD, percutaneous ASD closure is the most frequently used closure method, and offers results comparable with surgical closure (9,(27)(28)(29). The procedure is guided by either TEE or intracardiac echo.…”
Section: Part VI Surgical/interventional Technical Optionsmentioning
confidence: 99%
“…Recently, Redington et al [14] reported their experience in transcatheter closure of ASD using ASO in 20 adults. Most of their patients were symptomatic with effort intolerance or paradoxical embolism while the majority of our patients were asymptomatic.…”
Section: Discussionmentioning
confidence: 98%